On Our Minds : How Evolutionary Psychology Is Reshaping the Nature versus Nurture Debate - Gander, Eric (Book collections on Project MUSE., 2003)
"In On Our Minds, Eric M. Gander examines all sides of the public debate between evolutionary psychologists and their critics. Paying particularly close attention to the popular science writings of Steven Pinker, Edward O. Wilson, Richard Dawkins, and Stephen Jay Gould, Gander traces the history of the controversy, succinctly summarizes the claims and theories of the evolutionary psychologists, dissects the various arguments deployed by each side, and considers in detail the far-reaching ramifications - social, cultural, and political - of this debate. Gander's lucid and highly readable account concludes that evolutionary psychology now holds the potential to answer our oldest and most profound moral and philosophical questions, fundamentally changing our self-perception as a species."--Jacket